Tantangan Pengelolaan Wisata Edukasi Di Museum Batik Danar Hadi - Made Prasta Yostitia Pradipta; Putra, Heddy Shri Ahimsa; Tri Kuntoro Priambodo; Hendrie Adji Kusworo (Sekolah Tinggi Pariwisata Sahid Surakarta, 2026)
The Danar Hadi Batik Museum (MBDH) is a leading cultural tourist destination in Surakarta that is widely used by schools as an outdoor learning space. However, the intensity of these visits has not been fully accompanied by structured educational tourism management in line with the museum's function as an educational institution. This study aims to analyse the challenges of educational tourism management at MBDH by examining the gap between existing practices and the ideal museum based on Government Regulation No. 66 of 2015. The analysis focuses on five elements of educational tourism, namely learning objectives, narrative-based collection content, delivery strategies, active interaction, and learning reflection and evaluation. This study uses a qualitative approach with a case study method through observation of visits by primary, junior high, and senior high school students, in-depth interviews with museum managers and guides, and analysis of museum regulations. The results show that educational tourism at MBDH is still dominated by guided informative visits, with knowledge transfer that has not been systematically designed. The absence of an educational master plan, limited integration of spatial narratives, dominance of oral methods, lack of active interaction, and absence of cognitive evaluation are the main challenges in management. This study concludes that a transformation in the management of educational tours is necessary for the museum to function as a meaningful and sustainable centre for cultural learning.